2006
DOI: 10.1051/ocl.2006.0047
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation et immunité : implications dans l’obésité et le diabète de type 2

Abstract: The evidences have been increasingly accumulated on the implication of inflammatory mediators like tumor necrosis factor-␣ (TNF-␣) and interleukin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 103 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…The marked inflammation leading to immunosuppression in obesity seems to favor viral infections [14][15][16]. Sheridan et al [17] observed that high body mass index (BMI) was associated with a high decline in influenza antibody titers and decreased CD8 + T-cell activation after 12 months post-vaccination.…”
Section: Obesity and Reduced Viral Protectionmentioning
confidence: 99%
“…The marked inflammation leading to immunosuppression in obesity seems to favor viral infections [14][15][16]. Sheridan et al [17] observed that high body mass index (BMI) was associated with a high decline in influenza antibody titers and decreased CD8 + T-cell activation after 12 months post-vaccination.…”
Section: Obesity and Reduced Viral Protectionmentioning
confidence: 99%
“…Additionally, obesity which is a major risk factor of several chronic diseases, including cardiovascular complications, diabetes, cancer, kidney dysfunction, etc., is also associated with a higher risk of respiratory tract infections, and hence the virus installation. Actually, an increase in adiposity has been shown to modify the integrity of the respiratory epithelium, which could lead to dysfunction of the respiratory tract (Honce and Schultz-Cherry, 2019) with an inflammatory response resulting in immunosuppression that could promote viral infections (Khan, 2006). In term of oro-sensory perception, olfaction or taste disorders can lead to weight gain or to an aggravation of the infection by distorting the feeling of food satiation (Tomassini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%